Bullshit jobs - Graeber, David (Simon & Schuster, 2018)
"Does your job make a meaningful contribution to the world?" David Graeber asked this question in a playful, provocative online essay titled On the Phenonmenon of Bullshit Jobs. He defined a bullshit job as 'a form of paid employment that is so completely pointless, unnecessary, or pernicious that even the employee cannot justify its existence, even though as part of the conditions of employment, the employee feels obliged to pretend that this is not the case.' After a million views in seventeen different languages, people all over the world are still debating the answer. . . . Graeber, in his singularly searing and illuminating style, identifies the five types of bullshit jobs and argues that when 1 percent of the population controls most of a society's wealth, they control what jobs are 'useful' and 'important.' . . . Graeber illustrates how nurses, bus drivers, musicians, and landscape gardeners provide true value, and what it says about us as a society when we look down upon them. Using arguments from some of the most revered political thinkers, philosophers, and scientists of our time, Graeber articulates the societal and political consequences of these bullshit jobs. Depression, anxiety, and a warped sense of our values are all dire concerns. He provides a blueprint to undergo a shift in values, placing creative and caring work at the center of our culture, providing the meaning and satisfaction we all crave."--Jacket.